Strategi Cooperative Learning Pada Pembelajaran Menulis Puisi untuk Meningkatkan Interaksi Sosial Di Kelas Inklusif - Hawa, Masnuatul; Ika Rahmawati, Oktha; Ninda Johanes, Sevi; Zahra’, Kharidatuz (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Learning strategies play a crucial role in creating effective and inclusive learning experiences, particularly in poetry writing instruction, which requires studentsâ€™ social sensitivity and emotional engagement. This study aims to describe the implementation of the Cooperative Learning strategy in poetry writing instruction to enhance students’ social interaction in inclusive classrooms. The research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that Cooperative Learning is effective in fostering positive social interaction through heterogeneous group work, fair role distribution, and structured interpersonal communication. In addition to increasing studentsâ€™ appreciation of poetry, this strategy also cultivates empathy, a sense of responsibility, and social cohesion among students, including those with special educational needs. Thus, Cooperative Learning not only strengthens literary learning outcomes but also serves as a pedagogical approach that supports humanistic, democratic, and inclusive literary education.